2006
DOI: 10.1007/s10689-005-2577-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Genetic Counseling for Familial Cancer: A Systematic Review and Meta-Analysis

Abstract: Genetic counseling for familial cancer is associated with improvement in knowledge but does not have an adverse effect on affective outcomes. We urge further investigation of these findings through well-designed, well-reported, randomized controlled trials with suitable comparison groups and additional outcome measures [J Natl Cancer Inst 2004; 96:122-33].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
109
1
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 69 publications
9
109
1
10
Order By: Relevance
“…The primary outcome measure was anxiety, the reduction of which is regarded as a key counselling objective (Shaw et al, 1999;Brain et al, 2000;Meiser and Halliday, 2002) and a number of evaluations of genetic counselling for familial cancer have identified the pre-and postcounselling assessment of generalised anxiety as a main outcome measure (Cull et al, 1998Julian-Reynier et al, 1999;Brain et al, 2000;Kent et al, 2000;Bish et al, 2002;Bowen et al, 2004). Evidence from systematic reviews suggests that, overall, genetic counselling has the effect of significantly reducing patients' anxiety levels, at least in the short-term (Meiser and Halliday, 2002;Butow et al, 2003;Braithwaite et al, 2004). The a priori equivalence limits for the primary outcome (STAI) were set at a very strict level, and in reality they probably represent a smaller difference than would normally be considered clinically significant between two clinicians considered equally competent; however, results showed that some outcomes were considered 'equivalent' even at this strict level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary outcome measure was anxiety, the reduction of which is regarded as a key counselling objective (Shaw et al, 1999;Brain et al, 2000;Meiser and Halliday, 2002) and a number of evaluations of genetic counselling for familial cancer have identified the pre-and postcounselling assessment of generalised anxiety as a main outcome measure (Cull et al, 1998Julian-Reynier et al, 1999;Brain et al, 2000;Kent et al, 2000;Bish et al, 2002;Bowen et al, 2004). Evidence from systematic reviews suggests that, overall, genetic counselling has the effect of significantly reducing patients' anxiety levels, at least in the short-term (Meiser and Halliday, 2002;Butow et al, 2003;Braithwaite et al, 2004). The a priori equivalence limits for the primary outcome (STAI) were set at a very strict level, and in reality they probably represent a smaller difference than would normally be considered clinically significant between two clinicians considered equally competent; however, results showed that some outcomes were considered 'equivalent' even at this strict level.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge we assessed was not specific to cancer genetics, and our findings are consistent with genetic counselling delivered by either doctors or nurses being equally effective (or ineffective) in educating patients about breast cancer risk. Braithwaite et al (2004) suggest that genetic counselling can be effective in improving knowledge related to breast cancer genetics, compared with no counselling or counselling delivered by nongenetics specialists. However, the observed level of misunderstanding seen in this study suggests that more effective population interventions are required to improve general knowledge of breast cancer risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 The psychological adjustment of individuals undergoing genetic testing for cancer susceptibility has been studied extensively. [6][7][8] In general, no major long-term adverse psychological consequences seem to result from the genetic testing process with the exception of a consistently present subgroup of individuals who report distress. 7,9,10 Although what causes psychological difficulties for this subgroup is still unclear, it has been proposed that psychological adaptation should be analyzed not only at the individual perspective level but also in the context of the family interrelationships.…”
Section: Introductionmentioning
confidence: 99%